ANALISIS MINAT BELI KONSUMEN PADA PRODUK POINT COFFEE INDOMARET - Vieri Irawan (2020)
This research is a quantitative research that aims to determine the promotion, price and quality of product on purchase intention. The population in this study is a consumers who have experienced and purchased Indomaret Point Coffee product. The samples size was taken as many as 100 respondents, with a probability sampling method, simple random sampling. Data collection was carried out through the collection of google form questionnaires. The analysis technique used is the method PLS (Partial Least Square) analiysis method with SmartPLS 3.0 software. The results of this study indicate. (1) Promotion variable has a significant effect on purchase intention. (2) Price of importance is significant on purchase intentention. (3) Product quality variable is of significant importance on purchase intention.